KEBIASAAN MAKAN DAN ASUPAN ZAT GIZI MASYARAKAT HALMAHERA - Hadi Riyadi (Food and Nutrition Society of Indonesia, 2010)
Every community develops a specific socio-cultural aspect of food. The socio-cultural factor of food reflects the food consumption pattern of social life in the community. The study was carried out to analyze food habits and nutrients intake of people in Halmahera. This research was a survey design. This research was conducted in 10 villages in Halmahera Tengah and in 3 villages in East Halmahera. Sample size (n=304) was determined by simple random sampling without replacement formula. Primary data was collected in this study by interviewing respondents. The primary data was demography characteristics; food sources, preparation and processing; food taboo and preferences of children under five year old; and food consumption of households. The research showed that the communities in the research locations were agrarian communities in which their life depends on the surrounding nature. Like the population in Maluku in general, most population of Halmahera consumed sago and its processed products as its principal food sources including lempeng kasbi sago, tree lempeng sago, popeda sago, and others. The kinds of fish and foods not permitted to consume because of taboos were laying fish, nyoa fish, Rayfish, tuna, maleo and bee birds, pineapples and suanggi bananas. Some children under five liked sweet potato, taro, rice, porridge, cassava, and bananas. The average energy and protein level of sufficiency among the samples in both regencies was relatively good, except in Kobe Gunung Village and Sawai Itepo had lower level of energy and protein sufficiency than those in other villages. The nutrients with a low level of nutrient sufficiency in all villages included vitamin A, vitamin C and calcium.